Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1128/aem.70.8.4588-4595.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Administration of Escherichia coli O157:H7: Novel Model for Colonization of Ruminants

Abstract: Escherichia coli O157:H7 causes hemorrhagic colitis and life-threatening complications. Because healthy cattle are reservoirs for the bacterium, ruminant infection models have applications in analyzing the relationship between cattle and this human pathogen and in testing interventions to reduce or prevent bovine colonization with this bacterium. Current approaches often do not reliably mimic natural, long-term bovine colonization with E. coli O157:H7 in older calves and adult animals (ages that enter our food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 29 publications
7
65
1
Order By: Relevance
“…Mature ruminants are considered a reservoir for O157 and non-O157 STECs, with the amount and duration of shedding related to exposure dose [30,31], age [32] and mucosal factors [33]. Despite this information, it is unclear why one animal becomes infected while another does not.…”
Section: Discussionmentioning
confidence: 99%
“…Mature ruminants are considered a reservoir for O157 and non-O157 STECs, with the amount and duration of shedding related to exposure dose [30,31], age [32] and mucosal factors [33]. Despite this information, it is unclear why one animal becomes infected while another does not.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Shiga toxins do not affect either EHEC O157:H7 colonization of the terminal rectum in single strain rectal challenged cattle (Sheng et al 2006) or secretory responses in bovine ileal intestinal loops from older calves (Stevens et al 2002). The terminal rectum studies (Naylor et al 2003;Sheng et al 2004Sheng et al , 2006Low et al 2005;Lim et al 2007) have focused on the role of lymphoid tissue in the EHEC O157:H7 infection process in cattle without comparisons with absorptive epithelium in other intestinal sites despite the reported association of EHEC O157:H7 with small and large intestinal sites in challenged cattle (Cray and Moon 1995;Grauke et al 2002;Van Baale et al 2004). In a previous study, we reported that there were no differences in the dose-dependent colonization of small and large intestinal sites compared with the terminal rectum (Baines et al 2008, manuscript in preparation) and in this study, we add to this by showing that the small and large intestinal tissues also respond to EHEC O157:H7 secreted cytotoxins in a similar manner to that reported for a model system purported to better represent the response of ruminant systems to EHEC O157:H7 colonization (Robinson et al 2006).…”
Section: Ivoc Adherence Assaymentioning
confidence: 99%
“…These shedding patterns were suggested by Grauke et al (2002) to represent differences in EHEC O157:H7 colonization, and we recently confirmed this hypothesis (Baines et al 2008, manuscript in preparation). Other factors affect EHEC O157:H7 colonization in cattle including age (Cray and Moon 1995) and exposure dose (Besser et al 2001;Sheng et al 2004). Two EHEC effector molecules, Intimin and Tir, are important EHEC O157:H7 virulence factors, enhancing the magnitude and duration of shedding in calves and cattle (Dean-Nystrom et al 1998;Stevens et al 2002;Sheng et al 2006;Sinclair et al 2006) with the benefit derived from their involvement in the intimate attachment of bacteria to mucosal tissues.…”
Section: Ivoc Adherence Assaymentioning
confidence: 99%
See 2 more Smart Citations